Coco cups (Vegan ice cream) - Alvina, Nicole Jane D. Aves, Aldrin Louis F. Faustino, Nicka B. Lawingco, Julian Mae L. Macalintal, Sherem Nazareen S. Oliva, Angelica B. Palicpic, Sheree P. Raquin, Ronalyn R. Salva, Donna Mae F. 4 0 16; 5 (2023)
u
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2